Reliability of transcranial magnetic stimulation evoked potentials to detect the effects of theta-burst stimulation of the prefrontal cortex - Adriano H. Moffa; Stevan Nikolin; Donel Martin; Colleen Loo; Tjeerd W. Boonstra (NeuroImage: Reports)
Background: Transcranial magnetic stimulation (TMS) with simultaneous electroencephalography (EEG) is a novel method for assessing cortical properties outside the motor region. Theta burst stimulation (TBS), a form of repetitive TMS, can non-invasively modulate cortical excitability and has been increasingly used to treat psychiatric disorders by targetting the dorsolateral prefrontal cortex (DLPFC). The TMS-evoked potentials (TEPs) and local mean field power (LMFP) analyses have been used to evaluate local cortical excitability changes after TBS. However, it remains unclear whether TEPs can detect the neuromodulatory effects of TBS. Objectives: To confirm the reliability of TEP components and LMFP within and between sessions and to measure changes in neural excitability induced by intermittent (iTBS) and continuous TBS (cTBS) applied to the left DLPFC. Methods: Test-retest reliability of TEPs/LMFP and TBS-induced changes in cortical excitability were assessed in twenty-four healthy participants by stimulating the DLPFC in five separate sessions, once with sham and twice with iTBS and cTBS. EEG responses were recorded of 100 single TMS pulses before and after TBS, and the reproducibility measures were quantified with the concordance correlation coefficient (CCC). Results: The N100 and P200 components presented substantial reliability within the baseline block (CCCs>0.8) and moderate concordance between sessions (CCCmax> 0.6). Both N40 and P60 TEP amplitudes showed little concordance between sessions. Similar results were achieved using LMFP responses. Changes in TEP amplitudes after iTBS were marginally reliable for N100 (CCCmax = 0.52), P200 (CCCmax = 0.47) and P60 (CCCmax = 0.40), presenting only fair levels of concordance at specific time points. LMFP changes showed poor reproducibility after iTBS and cTBS. Conclusions: The present findings show that only the N100 and P200 components had good concordance between sessions. The reliability of earlier TEP components and LMF responses may have been affected by a sub-optimal removal of TMS-related artefacts. The poor reliability in detecting changes in neural excitability induced by TBS indicates that TEPs/LMFP do not provide a precise estimate of the changes in excitability in the DLPFC or, alternatively, that TBS did not induce consistent changes in neural excitability.